Composite material, preparation method of composite material, lining and preparation method of lining

By using polyamide matrix and glass fiber composite material as the inner lining of the polishing machine fixture, the problem of insufficient wear resistance of the inner lining in the prior art is solved, and higher polishing efficiency and surface flatness control are achieved, and production costs are reduced.

CN119119726APending Publication Date: 2024-12-13ZHONGHUAN ADVANCED (XUZHOU) SEMICONDUCTOR MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411388255.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The lining material of existing double-sided polishing machine fixtures is insufficiently wearable, resulting in excessive wear of the silicon wafer edge during the polishing process, affecting surface flatness and geometric parameters, and frequent replacement, increasing production costs.

Method used

The composite material consisting of 50% to 60% polyamide matrix and 40% to 50% glass fiber reinforcement is used as the lining material of the polishing machine fixture. It is prepared by injection molding to improve the tensile strength and hardness of the lining and reduce the lining Mechanical damage and optimize the diameter and ratio of glass fibers to match the hardness of the silicon wafer.

Benefits of technology

It significantly improves the control ability of the surface flatness of polished silicon wafers, reduces the surface flatness difference, extends the service life of the lining, reduces production costs, and improves the polishing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119726A_ABST
    Figure CN119119726A_ABST
Patent Text Reader

Abstract

The invention provides a composite material and a preparation method thereof, and a lining and a preparation method thereof. Based on the total mass of the composite material, the composite material comprises the following components in percentage by mass: 50-60% of a matrix; 40%-50% of a reinforcing agent; the matrix is polyamide, the reinforcing agent is filiform glass fiber, the fiber diameter of the glass fiber is D, and D is more than or equal to 5 microns and less than or equal to 25 microns. The polyamide provides excellent tensile strength, bending strength and rigidity for the composite material, and the glass fiber further enhances the mechanical strength of the composite material, so that the good mechanical performance of the composite material is ensured, the requirements of a clamp of a silicon wafer polishing machine on the hardness and wear resistance of a lining are met, and the geometric parameter control capability of a polished silicon wafer is effectively improved; the surface flatness difference of the same batch of silicon wafers is reduced, the polishing efficiency is improved, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a composite material and a preparation method thereof, and an inner lining of a polishing machine fixture and a preparation method thereof. Background Art

[0002] Double-sided polishing technology cleverly combines the dual effects of mechanics and chemistry to achieve a highly coordinated and balanced process. In terms of mechanical action, a precisely designed polishing machine and a polishing pad made of a specific material are used to apply appropriate pressure and rotation speed to physically grind and polish the surface of the silicon wafer, gradually flattening the uneven areas. The chemical action is reflected in the polishing liquid, which contains ingredients that react slightly with the surface of the silicon wafer. These reactions help to further soften or dissolve the tiny particles on the surface and accelerate the smoothing process of the surface. The two complement each other, ensuring both the high efficiency of polishing and the fine control of the silicon wafer surface, avoiding possible damage caused by over-polishing, and thus achieving an ideal surface state and surface flatness.

[0003] Among them, the fixture of the existing double-sided polishing machine directly contacts the edge of the silicon wafer, which has a great impact on the GBIR (Global Flatness Back Ideal Range) and SFQR (Site Flatness front least-squares Range) of the silicon wafer at the edge. A typical fixture usually consists of four parts, namely a stainless steel body, a diamond wear-resistant coating on the surface of the body, a lining, and a dovetail groove connecting the body and the lining. The lining of the fixture directly contacts the silicon wafer and supports and protects the edge of the silicon wafer during polishing. If the tensile strength and hardness of the fixture lining are low, it is easy to be worn during polishing. After wear, the edge of the silicon wafer loses the support and protection of the lining, and its edge will be excessively worn by the polishing pad, resulting in the removal amount of the silicon wafer edge being higher than the removal amount at other positions, and the edge of the silicon wafer is obviously concave, resulting in the deterioration of the geometric parameters of the edge of the silicon wafer. However, if the hardness of the fixture lining is too high, it will cause mechanical damage to the edge of the silicon wafer. It can be seen that the performance of the fixture lining material has a significant impact on the surface state and flatness of the silicon wafer after polishing. Among them, the existing double-sided polishing machine usually performs double-sided polishing on 12-inch silicon wafers.

[0004] At present, the inner lining of the polishing machine fixture is usually made of PVDF (polyvinylidene fluoride) material. PVDF material has the advantages of high thermal deformation temperature, high continuous heat resistance temperature, low difficulty in injection molding, and high yield after injection molding. However, its tensile strength and Rockwell hardness are low, resulting in poor wear resistance of PVDF material. PVDF material is easily worn during continuous polishing, which weakens the protective effect on the edge of the silicon wafer and causes the geometric parameters of the edge of the silicon wafer to deteriorate, resulting in the inner lining of the fixture having a short service life and frequent replacement, and a high cost of use.

[0005] In summary, the hardness and wear resistance of the lining material of the double-sided polishing machine need to be further improved. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one purpose of the present invention is to provide a composite material, which has better mechanical properties such as strength and hardness, can effectively improve the wear resistance of the polishing machine fixture lining prepared by the composite material, reduce the mechanical damage caused by the lining to the silicon wafer, effectively control and improve the surface flatness of the polished silicon wafer, and reduce the production cost.

[0007] In one aspect of the present invention, the present invention provides a composite material. According to an embodiment of the present invention, the composite material is suitable for a lining material of a polishing machine fixture, and based on the total mass of the composite material, the composite material comprises: 50% to 60% of a matrix; 40% to 50% of a reinforcing agent; 0 to 2% of an additive, wherein the matrix is ​​polyamide, the reinforcing agent is glass fiber, the glass fiber is filamentous, the fiber diameter of the glass fiber is D, and satisfies 5 microns ≤ D ≤ 25 microns.

[0008] Thus, the composite material of the above ratio is formed by the distribution of filamentary glass fibers of a certain diameter in a polyamide matrix, wherein the polyamide itself has the properties of high strength, good toughness, and wear resistance, and provides a matrix with good performance for the composite material. The tensile strength of the glass fiber itself is high, which can further enhance the mechanical strength of the composite material. Under the external force, the filamentary glass fiber of a certain diameter can effectively transmit and share the load of the polyamide when it is stressed, thereby ensuring the good mechanical properties of the composite material such as strength and hardness, so as to meet the requirements of the silicon wafer polishing machine fixture for the hardness and wear resistance of the lining material. The tensile strength and hardness of the polishing fixture lining prepared from the composite material are improved, and when the lining is prepared by injection molding, the addition of glass fibers helps to reduce the shrinkage and deformation of the composite material during the injection molding process, and helps to improve the dimensional stability and surface quality of the lining. In this way, the polishing machine lining using the composite material can effectively improve the control ability of the surface flatness of the polished silicon wafer, reduce the difference in the surface flatness of the same batch of polished silicon wafers, improve the polishing efficiency, and reduce production costs.

[0009] According to an embodiment of the present invention, the fiber length of the glass fiber is L, and satisfies 20*D≤L≤30*D.

[0010] According to an embodiment of the present invention, the glass fiber includes: a first glass fiber, the diameter of the first glass fiber is D1, and satisfies 5 microns ≤ D1 < 15 microns; a second glass fiber, the diameter of the second glass fiber is D2, and satisfies 15 microns ≤ D2 < 20 microns; and a third glass fiber, the diameter of the third glass fiber is D3, and satisfies 20 microns ≤ D3 < 25 microns.

[0011] According to an embodiment of the present invention, the composite material is used to polish a first silicon wafer, the resistivity of the first silicon wafer is 0.1 to 100 Ω·cm, and based on the total weight of the glass fibers in the composite material, the glass fibers include: 10% to 35% of first glass fibers; 30% to 70% of second glass fibers; and 10% to 35% of third glass fibers.

[0012] According to an embodiment of the present invention, the resistivity of the first silicon wafer is 0.1-10Ω·cm, and based on the total weight of the glass fiber in the composite material, the glass fiber includes: 10%-25% of the first glass fiber; 50%-70% of the second glass fiber; and 15%-35% of the third glass fiber.

[0013] According to an embodiment of the present invention, the resistivity of the first silicon wafer is 10 to 100 Ω·cm. Based on the total weight of the glass fibers in the composite material, the glass fibers include: 20% to 35% of first glass fibers; 30% to 60% of second glass fibers; and 10% to 35% of third glass fibers.

[0014] According to an embodiment of the present invention, the composite material is used to polish a second silicon wafer, the resistivity of the second silicon wafer is 0.01 to 0.00001 Ω·cm, and based on the total weight of the glass fiber in the composite material, the glass fiber includes: 20%-50% of the first glass fiber; 30%-50% of the second glass fiber; and 20%-40% of the third glass fiber.

[0015] According to an embodiment of the present invention, the resistivity of the second silicon wafer is 0.01-0.001Ω·cm, and based on the total weight of the glass fiber in the composite material, the glass fiber includes: 20%-40% of the first glass fiber; 40%-50% of the second glass fiber; and 20%-40% of the third glass fiber.

[0016] According to an embodiment of the present invention, the resistivity of the second silicon wafer is 0.001-0.0001Ω·cm, and based on the total weight of the glass fiber in the composite material, the glass fiber includes: 30%-40% of the first glass fiber; 35%-40% of the second glass fiber; and 20%-40% of the third glass fiber.

[0017] According to an embodiment of the present invention, the resistivity of the second silicon wafer is 0.0001-0.00001Ω·cm, and based on the total weight of the glass fiber in the composite material, the glass fiber includes: 40%-50% of the first glass fiber; 30%-35% of the second glass fiber; and 20%-40% of the third glass fiber.

[0018] In another aspect of the present invention, the present invention provides a method for preparing the composite material described above. According to an embodiment of the present invention, the method for preparing the composite material includes: heating and melting polyurethane to obtain a polyurethane melt, wherein the temperature of the heating and melting is greater than the melting point of polyamide and less than the melting point of glass fiber; mixing the glass fiber into the polyurethane melt to obtain a mixed melt; cooling and drying the mixed melt to obtain the composite material. In this way, the polyamide in the mixed melt is liquid, and the glass fiber is solid and filamentous, so that the glass fiber is distributed in the liquid polyamide. Among them, polyamide itself has the properties of high strength, good toughness, and wear resistance. A filamentous glass fiber of a certain diameter is distributed on the matrix of polyamide. The glass fiber is distributed in a dispersed manner. Under external force, the filamentous glass fiber can effectively transmit and share the load of polyamide when it is stressed, which not only strengthens the strength of the composite material but also enhances its wear resistance.

[0019] According to an embodiment of the present invention, the temperature of the heating and melting is 275°C to 325°C.

[0020] In another aspect of the present invention, the present invention provides a method for preparing a polishing machine fixture lining using the composite material described above. According to an embodiment of the present invention, the method for preparing the lining comprises: heating and melting the composite material to obtain a melt; injecting the melt into a mold cavity, and injecting the lining, wherein the mold cavity has at least 8 injection holes. Thus, in the above-mentioned preparation method, the polyamide itself has high strength, good toughness, wear resistance and other properties, which provides a matrix with good performance for the composite material; the high tensile strength of the glass fiber itself can further enhance the mechanical strength of the composite material, and the glass fiber can effectively transmit and share the load of the polyamide when it is stressed, thereby ensuring the good strength, hardness and other mechanical properties of the composite material, so as to meet the requirements of the silicon wafer polishing machine fixture for the hardness and wear resistance of the lining material. Moreover, when the lining is prepared by injection molding, during the injection molding process, the addition of glass fiber helps to reduce the shrinkage and deformation of the composite material, and helps to improve the dimensional stability and surface quality of the lining. In summary, the composite material for preparing the lining and the preparation method of the present invention can meet the requirements of the silicon wafer polishing machine fixture for the wear resistance, hardness and other properties of the lining. The polishing machine lining using the composite material can effectively improve the control capability of the surface flatness of the polished silicon wafer, reduce the difference in surface flatness of the same batch of polished silicon wafers, improve the polishing efficiency, and reduce the production cost. Moreover, the above-mentioned injection molding method has a mature and simple process and a high preparation efficiency.

[0021] In another aspect of the present invention, the present invention provides a lining for a polishing machine fixture. According to an embodiment of the present invention, the lining is prepared by the method described above. The lining using the composite material has good mechanical properties such as strength and hardness to meet the requirements of the silicon wafer polishing machine fixture for the hardness and wear resistance of the lining material. The polishing machine lining using the composite material can effectively improve the control ability of the surface flatness of the polished silicon wafer, reduce the difference in the surface flatness of the same batch of polished silicon wafers, improve the polishing efficiency, and reduce the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0023] Figure 1 is a schematic structural diagram of a mold cavity in one embodiment of the present invention;

[0024] Figure 2 is a schematic structural diagram of a mold cavity in another embodiment of the present invention;

[0025] Figure 3 is a schematic diagram of a liner in yet another embodiment of the present invention;

[0026] Figure 4is a test chart of GBIR of the polished silicon wafers in Example 12 and Comparative Example 3;

[0027] Figure 5 1 is a test chart of SFQR of the polished silicon wafers in Example 12 and Comparative Example 3;

[0028] Figure 6 is a test chart of GBIR of the polished silicon wafers in Example 13 and Comparative Example 4;

[0029] Figure 7 It is a test chart of SFQR of the polished silicon wafers in Example 13 and Comparative Example 4. DETAILED DESCRIPTION

[0030] Below will be explained with reference to embodiment of the present invention.It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention.In the embodiment, if no specific technology or condition is indicated, it is carried out according to the technology or condition described in the document in this area or according to the product specification.The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be purchased from the market.

[0031] The inventors found that in order to solve the wear resistance problem of the lining material, it is indeed necessary to improve the hardness of the lining material. However, if the hardness of the lining material is too high, it will cause mechanical damage to the silicon wafer, such as cracks and fragments (the reason is that the lining material is in direct contact with the edge of the silicon wafer). The lining material needs to meet the higher hardness while avoiding mechanical damage. After research, the inventor introduced hardness and tensile strength parameters to evaluate the performance of the material. At present, the lining material of the silicon wafer polishing machine fixture is usually PVDF. The tensile strength of PVDF is generally 40-60MPa, and the Rockwell hardness of PVDF is generally around 80. In the actual continuous polishing process, PVDF material is easy to wear, causing the geometric parameters of the edge of the silicon wafer to deteriorate, and the lining material is frequently replaced, affecting production costs. In order to solve the existing technical problems, the inventors have developed a new composite material for the lining of the polishing machine fixture. The specific plan is as follows:

[0032] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0033] In one aspect of the present invention, the present invention provides a composite material. According to an embodiment of the present invention, the composite material is suitable for the lining material of the polishing machine fixture. Based on the total mass of the composite material, the composite material includes: 50% to 60% (such as 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, etc.) of the matrix; 40% to 50% (such as 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, etc.) of the reinforcing agent; 0 to 2% (such as 0, 0.5%, 1.0%, 1.5%, 2.0%, etc.) of the additive, wherein the matrix is ​​polyamide, the reinforcing agent is glass fiber, the glass fiber is filamentous, the fiber diameter of the glass fiber is D, and satisfies 5 microns ≤ D ≤ 25 microns.

[0034] Thus, in the composite material of the above ratio, polyamide is used as a resin matrix, and glass fiber is used as a reinforcing agent. The glass fiber is short-filamentous rather than continuous long-filamentous, and is dispersedly distributed in the matrix of polyamide. Additives are added to promote the fusion and connection of polyamide and glass fiber. Polyamide is a thermoplastic resin, and the molecular chain contains repeated amide groups (-CONH-), and the connecting group includes a relatively long carbon chain. Polyamide itself has high strength, good toughness, wear resistance and other properties, and provides a matrix with good performance for the composite material. The tensile strength of the glass fiber itself is relatively high, and the mechanical strength of the composite material can be further enhanced. In particular, under external forces, the glass fiber can effectively transmit and share the load of the polyamide when it is stressed, thereby ensuring that the composite material has good mechanical properties such as strength and hardness, and meets the requirements of the lining material of the silicon wafer polishing machine fixture for hardness and wear resistance.

[0035] The composite material provided by the present invention has a tensile strength of 80.0-100 MPa and a Rockwell hardness of 120-160. Its hardness, wear resistance and service life are significantly better than those of PVDF. Moreover, the composite material can still maintain strong strength and rigidity at a relatively high temperature. Its thermal deformation temperature is about 150° C. and can be used continuously at 100° C. (the actual temperature during the polishing process is usually 25-50° C.). It can be seen that the composite material has good mechanical properties and can meet the requirements for the material use temperature during the polishing process.

[0036] Through research, it is found that the higher the content of glass fiber, the higher the tensile strength and hardness of the composite material. In order to achieve the tensile strength and Rockwell hardness requirements of the above-mentioned composite material, the ratio of polyamide to glass fiber is adjusted. When the polyamide is 50%-60% and the glass fiber is 40%-50% according to the mass percentage, the composite material obtained by the ratio has good mechanical properties such as hardness and wear resistance. If the glass fiber content is too low, the tensile strength and hardness of the composite material will be too low, and the hardness and wear resistance requirements of the lining material of the polishing machine fixture will not be met. If the glass fiber content is too high, the polyamide content will be too low, which will weaken the strength and wear resistance of the composite material matrix and fail to meet the wear resistance requirements of the lining material of the polishing machine fixture.

[0037] According to an embodiment of the present invention, the fiber diameter of the glass fiber is 5 to 25 microns, such as 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 18 microns, 20 microns, 23 microns or 25 microns. The inventors also found that when the mass percentage of the glass fiber remains unchanged, the fiber diameter of the glass fiber directly affects the tensile strength and hardness of the composite material. The higher the proportion of glass fibers with larger diameters in the glass fibers, the higher the tensile strength and hardness of the composite material.

[0038] In an embodiment of the present invention, according to different fiber diameters of the glass fibers, the glass fibers include a first glass fiber, a second glass fiber and a third glass fiber, wherein the diameter D1 of the first glass fiber satisfies 5 microns ≤ D1 < 15 microns; the diameter D2 of the second glass fiber satisfies 15 microns ≤ D2 < 20 microns; and the diameter D3 of the third glass fiber satisfies 20 microns ≤ D3 < 25 microns.

[0039] The above embodiment can be understood as follows: when the mass percentage of glass fiber in the composite material is 40%, the glass fiber composition of embodiment (a) is 35% of the first glass fiber, 45% of the second glass fiber and 20% of the third glass fiber, while the glass fiber composition of embodiment (b) is 45% of the first glass fiber, 35% of the second glass fiber and 20% of the third glass fiber, then the tensile strength and hardness of the composite material composed of embodiment (a) are greater than the tensile strength and hardness of the composite material of embodiment (b). In other words, under the condition of maintaining the wear resistance requirements, the tensile strength and hardness of the composite material can be fine-tuned by adjusting the fiber diameter of the glass fiber, so that its hardness is close to the hardness of the silicon wafer to be polished, which can effectively reduce mechanical damage.

[0040] The glass fibers of the above fiber diameters can be uniformly mixed with the polyamide matrix, and facilitate the flow of the injection molding liquid during the injection molding process of preparing the liner. It should be noted that the diameters of the glass fibers in the composite material can be uniform or unequal, as long as they are between 5 microns and 25 microns.

[0041] In some embodiments of the present invention, additives include but are not limited to colorants, antioxidants, coupling agents, and auxiliary additives such as promoters that can promote the fusion and connection of polyamide and glass fiber. The specific additives can be flexibly selected by those skilled in the art according to the actual needs, and no limitation is made here.

[0042] According to some embodiments of the present invention, the polyamide is polyhexamethylene adipamide (nylon 66, PA66). Polyhexamethylene adipamide is prepared by polycondensation of adipic acid and hexamethylenediamine, and contains repeated amide groups (-CONH-) in the molecular chain, and the connecting group includes a longer carbon chain. PA66 has excellent tensile strength, bending strength and rigidity, so it can better improve the mechanical properties of the composite material to meet the requirements of the silicon wafer polishing machine fixture for the mechanical properties of the lining material.

[0043] According to some embodiments of the present invention, the fiber length of the glass fiber is L and satisfies 20*D≤L≤30*D. The glass fiber is shorter and in the form of short filaments, which makes it easier for the injection liquid to flow and for the glass fiber to be evenly distributed during the injection molding process.

[0044] In the embodiments of the present invention, different doping concentrations will result in silicon wafers with different resistivities. A low doping concentration will have a small effect on the crystal structure of the silicon wafer, and the hardness of the lightly doped silicon wafer is mainly determined by the crystal structure of silicon; a high doping concentration will significantly change the crystal structure and electron distribution of the silicon wafer, thereby affecting its mechanical properties such as hardness.

[0045] According to an embodiment of the present invention, in order to avoid mechanical damage between the polished silicon wafer and the inner liner, different inner liners are used for polished silicon wafers of different hardness (wherein the above-mentioned composite material is applied to the inner liner of the polishing machine fixture). The optimal adaptation condition between the polished silicon wafer and the inner liner is: when the hardness of the inner liner is less than the hardness of the polished silicon wafer, the closer the strength and hardness of the inner liner are to the strength and hardness of the polished silicon wafer, the better the matching of the two. Therefore, in order to better improve the quality and efficiency of silicon wafer polishing, the content of glass fibers of different fiber diameters in the composite material can be adjusted according to the resistivity of the required polished silicon wafer, so as to obtain composite materials and inner liners of different strengths and hardnesses, as follows:

[0046] In some embodiments, the composite material is used to polish a first silicon wafer, the resistivity of the first silicon wafer is 0.1-100 Ω·cm, and based on the total weight of glass fibers in the composite material being 40%-50%, the glass fibers include: 10%-35% (for example, 10%, 12%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, etc.) of first glass fibers; 30%-70% (for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.) of second glass fibers; and 10%-35% (for example, 10%, 12%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, etc.) of third glass fibers. According to the above ratio requirements, the tensile strength of the obtained composite material is 88-100MPa, such as 100MPa, 99MPa, 98MPa, 97MPa, 96MPa, 95MPa, 94MPa, 93MPa, 92MPa, 90MPa, 88MPa, etc., and the Rockwell hardness is 130-160, such as 130, 133, 135, 138, 140, 145, 150, 155, 160, etc. It can be seen that the glass fiber with the above ratio is helpful to obtain a composite material with high tensile strength and Rockwell hardness to meet the needs of polishing high resistivity silicon wafers. When the lining prepared by the composite material with the above ratio is used to polish silicon wafers, the geometric parameters of the polished silicon wafers can be significantly improved. Compared with the lining made of PVDF material, the GBIR of the silicon wafer is reduced by 30%-40%, and the SFQR is reduced by 40%-45% when the lining made of the composite material of the present invention is used to polish silicon wafers. It can be seen that when the lining prepared by the composite material of the present invention is used to polish silicon wafers, the control ability of the surface flatness of the polished silicon wafers can be effectively improved, the difference in surface flatness of the same batch of polished silicon wafers can be reduced, and the polishing efficiency can be improved.

[0047] Among them, the explanation of the above-mentioned GBIR and SFQR is as follows: silicon wafers are processed using a fixture with a lining of PVDF material and a fixture with a lining of the composite material of the present invention, respectively, and the same number of silicon wafers, such as 200 wafers, are processed respectively. Data analysis shows that the GBIR of silicon wafers processed by the fixture with a lining of the composite material of the present invention is 30%-40% lower than the GBIR of silicon wafers processed by the fixture with a lining of PVDF material, and the SFQR of silicon wafers processed by the fixture with a lining of the composite material of the present invention is 30%-40% lower than the SFQR of silicon wafers processed by the fixture with a lining of PVDF material.

[0048] In some embodiments, the first silicon wafer is a lightly doped silicon wafer, such as a lightly boron doped silicon wafer.

[0049] Further, in some specific embodiments, when the resistivity of the first silicon wafer is 0.1-10Ω·cm (for example, 0.1Ω·cm, 0.2Ω·cm, 0.5Ω·cm, 0.8Ω·cm, 1.0Ω·cm, 2.0Ω·cm, 3.0Ω·cm, 4.0Ω·cm, 5.0Ω·cm, 6.0Ω·cm, 7.0Ω·cm, 8.0Ω·cm, 9.0Ω·cm, 9.5Ω·cm, 9.9Ω·cm, 10Ω·cm, etc.), based on the total weight of the glass fiber in the composite material being 40%-50%, the glass fiber includes: 10%-25% of first glass fiber; 50%-70% of second glass fiber; and 15%-35% of third glass fiber. In other specific embodiments, when the resistivity of the first silicon wafer is 10-100Ω·cm (for example, 10Ω·cm, 15Ω·cm, 17Ω·cm, 20Ω·cm, 23Ω·cm, 25Ω·cm, 28Ω·cm, 30Ω·cm, 35Ω·cm, 40Ω·cm, 45Ω·cm, 50Ω·cm, 55Ω·cm, 60Ω·cm, 65Ω·cm, 70Ω·cm, 75Ω·cm, 80Ω·cm, 85Ω·cm, 90Ω·cm, 95Ω·cm, 99Ω·cm, 100Ω·cm, etc.), based on the total weight of the glass fiber in the composite material, the glass fiber includes: 20%-35% of the first glass fiber; 30%-60% of the second glass fiber; and 10%-35% of the third glass fiber. In this way, the mass percentage of glass fibers with different fiber diameters can be adjusted according to the resistivity of the silicon wafer, thereby obtaining a better matching lining, so that the hardness of the lining is closer to the hardness of the first silicon wafer, which can significantly reduce the mechanical damage caused by the large difference in hardness, and also effectively improve the ability to control the surface flatness of the polished silicon wafer and improve the polishing efficiency.

[0050] It should be noted that the above-mentioned first silicon wafer has overlapping endpoint values ​​when divided according to resistivity. As mentioned above, when the resistivity of the first silicon wafer is 0.1~10Ω·cm, and when the resistivity of the first silicon wafer is 10~100Ω·cm, the glass fiber content in the two different silicon wafers is different. However, when the resistivity of the silicon wafer is the cross endpoint value of 10Ω·cm, the above-mentioned two different ratios can be adopted, that is, the glass fiber can include: 10%-25% of the first glass fiber; 50%-70% of the second glass fiber; and 15%-35% of the third glass fiber, or the glass fiber can include: 20%-35% of the first glass fiber; 30%-60% of the second glass fiber; and 10%-35% of the third glass fiber.

[0051] In other embodiments, the composite material is used to polish a second silicon wafer, the resistivity of the second silicon wafer is 0.01-0.00001Ω·cm, and based on the total weight of the glass fiber in the composite material being 40%-50%, the glass fiber includes: 20%-50% (for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.) of the first glass fiber; 30%-50% (for example, 30%, 35%, 40%, 45%, 50%, etc.) of the second glass fiber; and 20%-40% (for example, 20%, 25%, 30%, 35%, 40%, etc.) of the third glass fiber. According to the above ratio requirements, the tensile strength of the obtained composite material is 85-95MPa, such as 85MPa, 86MPa, 87MPa, 88MPa, 89MPa, 90MPa, 91MPa, 92MPa, 93MPa, 94MPa, 95MPa, etc., and the Rockwell hardness is 120-145, such as 120, 121, 122, 123, 124, 124, 126, 127, 128, 129, 130, 133, 135, 138, 140, 142, 145, etc. It can be seen that the glass fiber with the above ratio is helpful to obtain a composite material with high tensile strength and Rockwell hardness and suitable to meet the needs of more polished silicon wafers with lower resistivity. When the lining composed of this material is used to polish silicon wafers, the geometric parameters of the polished silicon wafers can be greatly improved. Compared with the lining made of PVDF material, when the lining of the present invention is used to polish silicon wafers, the GBIR of the silicon wafer can be reduced by 30%-35%, and the SFQR can be reduced by 20%-25%. It can be seen that when the lining prepared by the above-mentioned composite material of the present invention is used to polish silicon wafers, the ability to control the geometric parameters of the silicon wafers can be greatly improved, the surface flatness differences of silicon wafers in the same batch can be reduced, and the polishing efficiency of the silicon wafers can be improved.

[0052] In some embodiments, the second silicon wafer is a heavily doped silicon wafer, such as a heavily arsenic-doped silicon wafer.

[0053] Further, in some specific embodiments, when the resistivity of the second silicon wafer is 0.01-0.001Ω·cm (for example, 0.001Ω·cm, 0.002Ω·cm, 0.003Ω·cm, 0.004Ω·cm, 0.005Ω·cm, 0.006Ω·cm, 0.007Ω·cm, 0.008Ω·cm, 0.009Ω·cm, 0.01Ω·cm, etc.), based on the total weight of the glass fiber in the composite material, the glass fiber includes: 20%-40% of the first glass fiber; 40%-50% of the second glass fiber; and 20%-40% of the third glass fiber. In other specific embodiments, when the resistivity of the second silicon wafer is 0.001-0.0001Ω·cm (for example, 0.0001Ω·cm, 0.0002Ω·cm, 0.0003Ω·cm, 0.0004Ω·cm, 0.0005Ω·cm, 0.0006Ω·cm, 0.0007Ω·cm, 0.0008Ω·cm, 0.0009Ω·cm, 0.001Ω·cm, etc.), based on the total weight of the glass fiber in the composite material, the glass fiber includes: 30%-40% of the first glass fiber; 35%-40% of the second glass fiber; and 20%-40% of the third glass fiber. In other specific embodiments, when the resistivity of the second silicon wafer is 0.0001-0.00001Ω·cm (for example, 0.00001Ω·cm, 0.00002Ω·cm, 0.00003Ω·cm, 0.00004Ω·cm, 0.00005Ω·cm, 0.00006Ω·cm, 0.00007Ω·cm, 0.00008Ω·cm, 0.00009Ω·cm, 0.0001Ω·cm, etc.), based on the total weight of the glass fiber in the composite material, the glass fiber includes: 40%-50% of the first glass fiber; 30%-35% of the second glass fiber; and 20%-40% of the third glass fiber. In this way, the mass ratio of glass fibers with different fiber diameters can be accurately adjusted according to the resistivity of the silicon wafer, and the lining can be adapted to silicon wafers of different specifications, thereby meeting the requirements of wear resistance and hardness of the polishing machine fixture lining, effectively improving the polishing efficiency and enhancing the ability to control the flatness of the silicon wafer surface.

[0054] It should be noted that the above-mentioned second silicon wafers have overlapping endpoint values ​​when divided according to resistivity. As mentioned above, when the resistivity of the second silicon wafer is 0.01~0.001Ω·cm, when the resistivity of the second silicon wafer is 0.001~0.0001Ω·cm, and when the resistivity of the second silicon wafer is 0.0001~0.00001Ω·cm, the glass fiber contents in the three second silicon wafers with different resistivities are different. However, when the resistivity of the silicon wafer is the intersection endpoint value of 0.001Ω·cm, the above-mentioned two different ratios can be adopted. When the resistivity of the silicon wafer is the intersection endpoint value of 0.0001Ω·cm, the above-mentioned two different ratios can be adopted.

[0055] In another aspect of the present invention, the present invention provides a method for preparing the composite material as described above. According to an embodiment of the present invention, the method for preparing the composite material comprises:

[0056] T100: heating and melting polyurethane to obtain a polyurethane melt, wherein the heating and melting temperature is greater than the melting point of polyamide and less than the melting point of glass fiber; mixing the glass fiber into the polyurethane melt to obtain a mixed melt.

[0057] This step is specifically as follows: polyamide is used as a matrix, and when heated and melted in liquid, a polyamide melt is formed, and 40%-50% of glass fibers with a fiber diameter of 5 microns to 25 microns are evenly mixed in. The heating temperature at this time is 275°C to 325°C, which does not reach the melting point of the glass fibers. The glass fibers are in the form of solid filaments, short filaments rather than continuous filaments. At this time, the solid glass fibers acting as a reinforcing agent are evenly distributed in the liquid polyamide matrix, and the fusion of the two effectively improves the strength and hardness of the composite material.

[0058] Further, in some embodiments, the heating temperature is 275°C to 325°C, such as 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, etc. At the above temperature, the complete melting of the polyamide can be effectively guaranteed without melting the glass fiber. In this way, the polyamide in the melt is liquid, and the glass fiber is solid and filamentous, so that the glass fiber can be dispersed in the liquid polyamide, which helps to improve the mechanical strength of the composite material.

[0059] T200: The mixed melt is cooled and dried to obtain a composite material.

[0060] According to an embodiment of the present invention, in the above-mentioned preparation method, the polyamide in the mixed melt is in liquid state, and the glass fiber is in solid state and filamentous form, so that the glass fiber can be dispersed in the liquid polyamide, which helps to improve the mechanical strength of the composite material.

[0061] In some embodiments, there are no special requirements for the specific method of cooling and drying, and those skilled in the art can flexibly select it according to conventional technical means and actual needs.

[0062] In another aspect of the present invention, the present invention provides a method for preparing a polishing machine fixture lining using the composite material described above. According to an embodiment of the present invention, the method for preparing the lining comprises:

[0063] S100: heating and melting the composite material to obtain a melt.

[0064] In some specific embodiments, the specific steps of preparing the melt include: first, the composite material can be processed into solid particles, the solid particles are added to the hopper of the injection molding machine, and the solid particles are heated and melted again and plasticized into a uniform melt through the screw rotation and heating process. Among them, the heating temperature when the solid particles are heated and melted again is greater than the melting point of polyamide and less than the melting point of glass fiber, for example, 275°C to 325°C. In this way, the polyamide in the melt is liquid, and the glass fiber is solid and filamentous, so that the glass fiber can be dispersed in the liquid polyamide. Under the external force, the filamentous glass fiber can effectively transmit and share the load of the polyamide when it is under force, which not only strengthens the strength of the composite material but also enhances its wear resistance.

[0065] S200: Inject the melt into the mold cavity to obtain the lining by injection molding.

[0066] In some embodiments, the screw of the injection molding machine rapidly injects the melt plasticized in step S100 into the mold cavity under high pressure to obtain the liner by injection molding. Furthermore, the injection speed and pressure of the injection molding can be flexibly adjusted by those skilled in the art according to the actual process requirements, and no limitation is imposed here.

[0067] According to an embodiment of the present invention, the composite material of the above ratio is formed by distributing filamentary glass fibers of a certain diameter in a polyamide matrix, wherein the polyamide itself has the properties of high strength, good toughness, and wear resistance, and provides a matrix with good performance for the composite material. The tensile strength of the glass fiber itself is relatively high, which can further enhance the mechanical strength of the composite material. Under external forces, the filamentary glass fibers of a certain diameter can effectively transmit and share the load of the polyamide when subjected to force, thereby ensuring the good strength, hardness and other mechanical properties of the composite material to meet the requirements of the silicon wafer polishing machine fixture for the hardness and wear resistance of the lining material. The tensile strength and hardness of the polishing fixture lining prepared from the composite material are improved; moreover, when the lining is prepared by injection molding, during the injection molding process, the addition of glass fibers helps to reduce the shrinkage and deformation of the composite material, and helps to improve the dimensional stability and surface quality of the lining. In summary, the material and preparation method for preparing the lining of the present invention can meet the requirements of the silicon wafer polishing machine fixture for the wear resistance, hardness and other properties of the lining. The polishing machine lining using the composite material can effectively improve the control capability of the surface flatness of the polished silicon wafer, reduce the difference in surface flatness of the same batch of polished silicon wafers, improve the polishing efficiency, and reduce the production cost. Moreover, the above-mentioned injection molding method has a mature and simple process and a high preparation efficiency.

[0068] In the currently commonly used injection molding machine, one or more (for example, 3) mold cavities can be set in each injection molding groove, and one mold cavity is used to form a liner by injection molding. It is well known to those skilled in the art that the liner of the silicon wafer polishing machine fixture is an annular structure with a certain inner diameter and wall thickness, which is suitable for double-sided polishing of 300mm silicon wafers. Therefore, the mold cavity is also an annular structure, and the mold cavity has an injection hole for injecting the melt into the mold cavity. Usually, each mold cavity has four injection holes evenly distributed, and the plasticized melt is injected into the mold cavity through the injection holes of the mold cavity. However, the inventor found that the fluidity of the molten melt of the composite material of the present invention is poorer than the fluidity of PVDF in the prior art, so when a mold cavity with four injection holes is used, the melt cannot be quickly and evenly distributed in the mold cavity, that is, at a position far away from the injection hole, the lining prepared has pores or faults due to the poor fluidity of the melt, which seriously affects the mechanical properties such as the strength and hardness of the lining and the performance of the lining.

[0069] Based on the above technical problems, the inventors further improved the structure of the mold cavity for the composite material of the present invention, specifically:

[0070] According to an embodiment of the present invention, the spacing D between two adjacent injection holes in each mold cavity is less than or equal to 107±0.5mm. Therefore, the spacing between the injection holes is small, so that the melt of the composite material of the present invention can be quickly and evenly injected and distributed at any position in the mold cavity, so that the density of the composite material injected at any position is relatively uniform and there are no undesirable phenomena such as gaps or faults, thereby improving the uniformity and mechanical properties of the prepared lining. Among them, the spacing between the two adjacent injection holes refers to the chord length (straight line distance) between the two injection holes, as shown in 1.

[0071] The spacing between the two injection holes mentioned above can be understood as follows: the spacing between two adjacent injection holes in the present invention is closely related to the number of injection holes evenly distributed on the injection mold cavity. When a general double-sided polishing machine polishes a 300mm silicon wafer, the radial width h of the liner is 2mm, and the radius of the injection mold is about 151mm. When 8 injection holes are evenly opened in the injection mold cavity, the spacing between two adjacent injection holes is 107±0.5mm. When 12 injection holes are evenly opened in the injection mold cavity, the spacing between two adjacent injection holes is 79±0.5mm. When 16 injection holes are evenly opened in the injection mold cavity, the spacing between two adjacent injection holes is 59±0.5mm.

[0072] According to an embodiment of the present invention, each mold cavity 10 has at least 8 injection holes. Figure 1 , each mold cavity 10 has 8 injection holes (injection hole 111, injection hole 112, injection hole 113, injection hole 114, injection hole 115, injection hole 116, injection hole 117, injection hole 118). Preferably, injection holes 111 to 118 are evenly distributed in the mold cavity, and the yield rate of injection molded products obtained by using the mold cavity is increased to 50%-65%. In other specific embodiments of the present invention, refer to Figure 2 , each mold cavity has 12 injection holes. (Injection hole 121, injection hole 122, injection hole 123, injection hole 124, injection hole 125, injection hole 126, injection hole 127, injection hole 128, injection hole 129, injection hole 130, injection hole 131 and injection hole 132). Preferably, injection holes 121 to 132 are evenly distributed in the mold cavity, and the yield rate of injection molded products obtained by using this mold cavity is increased to more than 95%. As a result, the spacing between the injection holes can be effectively reduced, so that the melt of the composite material can be quickly and evenly injected and distributed at any position in the mold cavity, so that the density of the composite material injected at any position is relatively uniform and there are no undesirable phenomena such as gaps or faults, thereby improving the uniformity and mechanical properties of the prepared lining.

[0073] In another aspect of the present invention, the present invention provides a lining for a polishing machine fixture. According to an embodiment of the present invention, the lining is prepared from the composite material of the present invention by the method described above. The lining using the composite material has good mechanical properties such as strength and hardness to meet the requirements of the silicon wafer polishing machine fixture for the hardness and wear resistance of the lining material. The polishing machine lining using the composite material can effectively improve the control ability of the surface flatness of the polished silicon wafer, reduce the difference in the surface flatness of the same batch of polished silicon wafers, improve the polishing efficiency, and reduce the production cost.

[0074] According to an embodiment of the present invention, referring to Figure 3 The inner diameter d of the liner 100 is 250 mm to 350 mm, the radial width h of the liner is 1 mm to 3 mm, and the thickness (or the height of the liner) is 0.7 micrometers to 0.8 micrometers. The liner of the above size is prepared by the composite material of the present invention, and the obtained liner has good mechanical strength and uniform quality.

[0075] According to the embodiments of the present invention, the inner lining of the polishing machine fixture of the present invention has better mechanical strength and hardness, which can meet the specific requirements of the silicon wafer polishing machine fixture for the inner lining performance: when the inner lining is used to polish the silicon wafer, the better tensile strength and hardness of the inner lining make it less prone to wear, and the edge of the silicon wafer is supported and protected by the inner lining, thereby avoiding the removal amount of the edge of the silicon wafer being higher than the removal amount of other positions, the edge of the silicon wafer being obviously concave, and the geometric parameters of the edge of the silicon wafer being deteriorated; at the same time, the inner lining is adapted to the polished silicon wafer, and the hardness difference between the two is small, avoiding the undesirable phenomenon of mechanical damage to the edge of the silicon wafer. In this way, the ability to control the geometric parameters of the silicon wafer after polishing can be effectively improved, the uneven geometric parameter levels of the silicon wafer can be reduced, the surface flatness of the polished silicon wafer can be improved, the polishing efficiency can be improved, and the cost of polishing the silicon wafer can be reduced.

[0076] According to the embodiments of the present invention, the tensile strength of the lining of the present invention is 80MPa-100MPa, the Rockwell hardness is 120-160, and it can still maintain strong strength and rigidity at higher temperatures. Its thermal deformation temperature is around 150°C, and it can be used continuously under continuous heat resistance conditions of 100°C, which is sufficient to meet the use requirements of polishing silicon wafers.

[0077] Example

[0078] Examples 1 to 11 and Comparative Examples 1 and 2

[0079] The liner was prepared by injection molding. The raw materials, proportions and material properties of the composite material forming the liner are shown in Tables 1 and 2.

[0080] The liners in Examples 1 to 3 are used for polishing silicon wafers with heavy arsenic doping at different doping amounts, and the liners in Examples 4 and 5 are used for polishing silicon wafers with light boron doping at different doping amounts.

[0081] Among them, the distribution of the proportions of different diameters of glass fibers in Examples 6 to 11 and Comparative Examples 1 and 2 is consistent, including: 20% of the first glass fiber; 60% of the second glass fiber; and 20% of the third glass fiber, the polished silicon wafer is a lightly boron-doped silicon wafer, wherein the diameter of the first glass fiber is D1, and satisfies 5 microns ≤ D1 < 15 microns; the diameter of the second glass fiber is D2, and satisfies 15 microns ≤ D2 < 20 microns; and the diameter of the third glass fiber is D3, and satisfies 20 microns ≤ D3 < 25 microns.

[0082] Table 1

[0083]

[0084]

[0085] Table 2

[0086]

[0087] It can be seen from Table 1 and Table 2 that the liner in Examples 1 to 11 has suitable tensile strength and hardness, and is suitable for polishing silicon wafers with different doping elements and doping amounts. When the liner is used to polish the silicon wafers corresponding to the above embodiments, it is found that the continuously polished liner itself is not easy to wear, and the edge of the silicon wafer is well protected after polishing, without the undesirable phenomenon of excessive wear; in Comparative Example 1, due to the low content of glass fiber, its strength and hardness are small. When the liner is used to polish the silicon wafer, it is found that the wear resistance of the liner is poor, and the continuous polishing process makes the liner easily worn, which leads to serious excessive wear of the edge of the silicon wafer after polishing; in Comparative Example 2, due to the high content of glass fiber, its strength and hardness are relatively large. When the liner is used to polish the silicon wafer, it is found that the polishing process will cause mechanical damage to the edge of the silicon wafer, which is not conducive to obtaining a silicon wafer with better surface flatness.

[0088] Example 12

[0089] The liner in Example 4 was used to polish the lightly boron-doped silicon wafer, and the GBIR and SFQR of the polished silicon wafer were tested. The test results are shown in Figure 4 and Figure 5 .

[0090] Comparative Example 3

[0091] The lining made of PVDF material was used to polish a lightly boron-doped silicon wafer (the same silicon wafer as in Example 12), and the GBIR and SFQR of the polished silicon wafer were tested. The test results are shown in Figure 4 and Figure 5 .

[0092] It can be seen from comparative example 12 and comparative example 3 that the GBIR and SFQR in example 12 are much lower than those in comparative example 3, indicating that the use of the liner of the present invention can effectively improve the geometric parameters of the polished silicon wafer.

[0093] Example 13

[0094] The liner in Example 1 was used to polish the heavily arsenic-doped silicon wafer, and the GBIR and SFQR of the polished silicon wafer were tested. The test results are shown in Figure 6 and Figure 7 .

[0095] Comparative Example 4

[0096] The liner made of PVDF material was used to polish the heavily arsenic-doped silicon wafer (the same silicon wafer as in Example 13), and the GBIR and SFQR of the polished silicon wafer were tested. The test results are shown in Figure 6 and Figure 7 .

[0097] It can be seen from comparative example 13 and comparative example 4 that the GBIR and SFQR in example 13 are much lower than those in comparative example 4, indicating that the use of the liner of the present invention can effectively improve the geometric parameters of the polished silicon wafer.

[0098] It should be noted that the test methods for the above test results are:

[0099] The test method for tensile strength is: (GB / T 1447-2005) "Test method for tensile properties of fiber reinforced plastics";

[0100] The test method for Rockwell hardness is: (GB / T 3398.2-2008) "Determination of plastic hardness Part 2: Rockwell hardness";

[0101] GBIR test method is: using KLA's ws2+ equipment to measure, removing the edge 2mm measurement, the measurement setting is 26ⅹ8;

[0102] The SFQR test method is: use KLA's ws2+ equipment to measure, remove the edge 2mm measurement, and the measurement setting is 26ⅹ8.

[0103] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0104] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0105] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A composite material, characterized in that: The composite material is suitable for the lining material of the polishing machine fixture. Based on the total mass of the composite material, the composite material comprises: 50% to 60% of the matrix; 40% to 50% enhancer; 0-2% additives, Wherein, the matrix is ​​polyamide, the reinforcing agent is glass fiber, The glass fiber is filamentous, has a fiber diameter D, and satisfies 5 microns ≤ D ≤ 25 microns.

2. The composite material according to claim 1, characterized in that The fiber length of the glass fiber is L, and satisfies 20*D≤L≤30*D.

3. The composite material according to claim 1, characterized in that The glass fiber comprises: A first glass fiber, wherein the diameter of the first glass fiber is D1 and satisfies 5 microns ≤ D1 < 15 microns; A second glass fiber, wherein the diameter of the second glass fiber is D2 and satisfies 15 microns ≤ D2 < 20 microns; and The third glass fiber has a diameter D3 and satisfies 20 micrometers ≤ D3 < 25 micrometers.

4. The composite material according to claim 3, characterized in that The composite material is used for polishing a first silicon wafer, the resistivity of the first silicon wafer is 0.1 to 100 Ω·cm, and based on the total weight of the glass fibers in the composite material, the glass fibers include: 10%-35% first glass fiber; 30%-70% of a second glass fiber; and 10%-35% of the third glass fiber.

5. The composite material according to claim 4, characterized in that The resistivity of the first silicon wafer is 0.1 to 10 Ω·cm. Based on the total weight of the glass fiber in the composite material, the glass fiber includes: 10%-25% first glass fiber; 50%-70% of a second glass fiber; and 15%-35% of the third glass fiber.

6. The composite material according to claim 4, characterized in that The resistivity of the first silicon wafer is 10 to 100 Ω·cm. Based on the total weight of the glass fiber in the composite material, the glass fiber includes: 20%-35% first glass fiber; 30%-60% of a second glass fiber; and 10%-35% of the third glass fiber.

7. The composite material according to claim 3, characterized in that The composite material is used for polishing a second silicon wafer, the resistivity of the second silicon wafer is 0.01 to 0.00001 Ω·cm, and based on the total weight of the glass fiber in the composite material, the glass fiber comprises: 20%-50% first glass fiber; 30%-50% of a second glass fiber; and 20%-40% of the third glass fiber.

8. The composite material according to claim 7, characterized in that The resistivity of the second silicon wafer is 0.01 to 0.001 Ω·cm. Based on the total weight of the glass fiber in the composite material, the glass fiber includes: 20%-40% first glass fiber; 40%-50% of a second glass fiber; and 20%-40% of the third glass fiber.

9. The composite material according to claim 7, characterized in that The resistivity of the second silicon wafer is 0.001 to 0.0001 Ω·cm. Based on the total weight of the glass fiber in the composite material, the glass fiber includes: 30%-40% first glass fiber; 35%-40% of a second glass fiber; and 20%-40% of the third glass fiber.

10. The composite material according to claim 7, characterized in that: The resistivity of the second silicon wafer is 0.0001 to 0.00001 Ω·cm. Based on the total weight of the glass fiber in the composite material, the glass fiber includes: 40%-50% first glass fiber; 30%-35% of a second glass fiber; and 20%-40% of the third glass fiber.

11. A method for preparing the composite material according to any one of claims 1 to 10, characterized in that: include: Heat and melt the polyurethane to obtain a polyurethane melt, wherein the temperature of the heating and melting is greater than the melting point of the polyamide and less than the melting point of the glass fiber; Mixing the glass fiber into the polyurethane melt to obtain a mixed melt; The mixed melt is cooled and dried to obtain the composite material.

12. The method according to claim 11, characterized in that The heating and melting temperature is 275°C to 325°C.

13. A method for preparing a polishing machine fixture lining using the composite material according to any one of claims 1 to 10, characterized in that: include: heating and melting the composite material to obtain a melt; The melt is injected into a mold cavity to obtain the lining by injection molding, Wherein, the mold cavity is provided with at least 8 injection holes.

14. A lining for a polishing machine fixture, characterized in that: It is prepared by the method according to claim 13.